2019
DOI: 10.33230/jps.7.1.2018.6997
|View full text |Cite
|
Sign up to set email alerts
|

Perbandingan Efektivitas Teh Hitam, Nanas dan Pepaya Sebagai Bahan Marinasi terhadap Kualitas Daging Sapi

Abstract: Tujuan penelitian ini adalah untuk mengetahui pengaruh teh hitam, nanas dan pepaya sebagai bahan marinasi terhadap kualitas daging sapi. Bahan marinasi yang digunakan dalam penelitian ini adalah larutan teh hitam, buah nanas dan papaya masing-masing sebanyak 20% dari berat daging. Penggunaan air perasan nanas dan papaya berperan sebagai pembanding terhadap efektifitas teh hitam terhadap kadar protein, nilai pH dan keempukan daging sapi. Hasil penelitian menunjukkan bahwa kadar protein daging sapi yang dimarina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Based on the results of previous research [23] regarding brahman cross beef, the highest yellowness value (b*) was found in the withering of pineapple waste for one month, and the lowest average was in the withering of pineapple waste for two months. Based on the analysis of variance, the results were not significantly different (P > 0.05) from the yellowness value.…”
Section: Yellowness (*B)mentioning
confidence: 97%
See 1 more Smart Citation
“…Based on the results of previous research [23] regarding brahman cross beef, the highest yellowness value (b*) was found in the withering of pineapple waste for one month, and the lowest average was in the withering of pineapple waste for two months. Based on the analysis of variance, the results were not significantly different (P > 0.05) from the yellowness value.…”
Section: Yellowness (*B)mentioning
confidence: 97%
“…The population of ducks in Indonesia in 2021 will reach 44,198.05 compared to the population in 2020, which only reached 41,116. 23.…”
Section: Introductionmentioning
confidence: 99%